2014
DOI: 10.3109/03009742.2014.918651
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between smoking, increased serum levels of anti-CCP antibodies, rheumatoid factors, and erosive joint disease in patients with early, untreated rheumatoid arthritis

Abstract: Shared epitopes and smoking were associated with the production of anti-CCP antibodies and rheumatoid factors of IgM and IgA isotypes, which again were associated with erosive disease at presentation only in smokers. As shared epitopes and smoking were not directly associated with erosive disease, smoking may enhance the development of erosive disease in RA at different levels or through separate pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…36 In a recent study of treatment-naïve adults with early RA, RF IgM, RF IgA and anti-CCP positivity were associated with erosive disease among ever smokers but not among never smokers. 38 In our communitybased cohort, we found that smoking modified the associations of RF IgM and anti-CCP-but not RF IgA-with HAA and ILA. Our data suggest that RF IgA might lead to lung injury, inflammation and fibrosis in a smoking-independent fashion, while RF IgM and anti-CCP might require concomitant or prior cigarette smoking before ILD pathology develops.…”
Section: Discussionmentioning
confidence: 62%
“…36 In a recent study of treatment-naïve adults with early RA, RF IgM, RF IgA and anti-CCP positivity were associated with erosive disease among ever smokers but not among never smokers. 38 In our communitybased cohort, we found that smoking modified the associations of RF IgM and anti-CCP-but not RF IgA-with HAA and ILA. Our data suggest that RF IgA might lead to lung injury, inflammation and fibrosis in a smoking-independent fashion, while RF IgM and anti-CCP might require concomitant or prior cigarette smoking before ILD pathology develops.…”
Section: Discussionmentioning
confidence: 62%
“…In genetically predisposed individuals, protein citrullination poses the potential risk of production of anticitrullinated peptide/protein antibodies (ACPA), which are strongly associated with development of RA [31,32]. In this context, the combination of current smoking and possession of HLA-DRB1 shared epitope (SE) alleles, both of which are independently associated with RA, is closely associated with the appearance of ACPA, an event which precedes, and is predictive of, the development of RA [33][34][35][36][37][38]. The specificity of ACPA for their target citrullinated proteins appears to increase closer to disease onset and progression [37].…”
Section: Smoking and Ramentioning
confidence: 99%
“…In this context, the combination of current smoking and possession of HLA-DRB1 shared epitope (SE) alleles, both of which are independently associated with RA, is closely associated with the appearance of ACPA, an event which precedes, and is predictive of, the development of RA [33][34][35][36][37][38]. The specificity of ACPA for their target citrullinated proteins appears to increase closer to disease onset and progression [37]. In the case of patients with early-onset RA, previous smoking is associated with a dose-dependent occurrence of ACPA in both the lungs and circulation [35,39].…”
Section: Smoking and Ramentioning
confidence: 99%
“…[3][4][5][6] Autoimmune antibodies such as rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) have prognostic significance for the development of RA. 7 Relationship between smoking and production of RF and anti-CCP has been reported. 8 RF positivity is found in 70-80% of patients with RA 9 and frequency of RF positivity was shown to be higher in smokers in the general population and long-term smokers among patients with RA.…”
mentioning
confidence: 99%
“…12 There are studies with conflicting results that determined a relationship between smoking and disease activity, radiologic progression and response to treatment. 4,7,8,13 In our knowledge, no study has been conducted with Turkish RA patients investigating the relationship between smoking and joint damage, disease activity and disability. Therefore, in this study, we aimed to investigate the relationship between smoking and structural damage, autoimmune antibodies, and disability in RA patients.…”
mentioning
confidence: 99%